PEMBERDAYAAN IBU HAMIL DAN KADER KESEHATAN DALAM PEMANFAATAN BUKU KIA UNTUK DETEKSI DINI PENYULIT PERSALINAN - Kurniati, Citra Hadi (Universitas Muhammadiyah Tangerang, 2021)
The KIA handbook is one of the documentation tools used for early detection of complications in childbirth. It is very important for pregnant women to study this MCH handbook so that if an abnormality occurs, they can immediately contact the nearest health worker. Health cadres are people who are closest to the community and often interact with the community. Cadres often meet with pregnant women, so it is easy to convey things related to pregnancy and the problems faced by pregnant women. This activity aims to improve the knowledge and skills of pregnant women and health cadres in early detection of complications in childbirth through the KIA Handbook. Activities carried out for pregnant women and health cadres during the class for pregnant women. Starting with a pretest related to the early detection of complications in labor, then continued with counseling and given skills related to the use of KIA handbooks, followed by a discussion and ended with a posttest. There is an increase in knowledge and skills in early detection of complications in childbirth through the KIA Handbook for pregnant women and health cadres based on the average result between pretest 75 and post test with a value of 90. Providing counseling and training on the use of early detection of labor complications can increase knowledge and skills in the use of KIA handbooks.